(untitled) (Research, Society and Development, 2021)
Introduction: We call cancer a chain of diseases that have together an imbalance in cell evolution and division. Abnormal cells can expand and enter other body structures, in a course called metastasis. Objective: To describe the importance of nursing care for cancer patients. Methodology: This study is an integrative literature review with a qualitative approach. The following inclusion criteria were defined: articles indexed in full and available for reading, in Portuguese and full text, with a time frame of 5 years (2016 to 2021). As exclusion criteria, repeated articles or articles that were not in accordance with the proposed theme were discarded. Results and discussions: Nursing is based on the duty to comprehensiveness, which is carried out through support, connection and communication and is assured in the recognition of insufficiencies in care exposed by users and their families, as it is an action centered on the individual and not exclusively in the methodology. Final considerations: The oncology area is a specialization constituted by several obstacles from research, surgeries, therapeutic models and continuous medical innovations, which requires the preparation of health professionals, as it is of great scientific and technical complexity.